2015
DOI: 10.1074/jbc.m114.608158
|View full text |Cite
|
Sign up to set email alerts
|

PTH1–34 Blocks Radiation-induced Osteoblast Apoptosis by Enhancing DNA Repair through Canonical Wnt Pathway

Abstract: Background: PTH1-34 alleviates radiation-induced osteoporosis in a preclinical radiotherapy model. Results: PTH1-34 attenuates radiation damage on osteoblasts by increasing Ku70 amount, accelerating DNA repair, and suppressing osteoblast apoptosis. Pathway analyses identify canonical Wnt pathway as an important mediator. Conclusion: PTH1-34 blocks radiation-induced osteoblast apoptosis through activation of ␤-catenin. Significance: PTH1-34 or Wnt agonist could be possible therapy for radiation-induced osteopor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
48
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 53 publications
5
48
0
Order By: Relevance
“…Our study builds on previous work implicating β-catenin in the regulation of genome stability (Aoki et al, 2007;Dose et al, 2014) and in the DNA damage response (Chandra et al, 2015;Priolli et al, 2013;Tavana et al, 2013;Xu et al, 2008;Zhang et al, 2011). Indeed, our data align well with these previous reports.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study builds on previous work implicating β-catenin in the regulation of genome stability (Aoki et al, 2007;Dose et al, 2014) and in the DNA damage response (Chandra et al, 2015;Priolli et al, 2013;Tavana et al, 2013;Xu et al, 2008;Zhang et al, 2011). Indeed, our data align well with these previous reports.…”
Section: Discussionsupporting
confidence: 90%
“…This is in agreement with numerous studies showing that gain-of-function mutations in β-catenin signaling and loss of α-catenin regulation are prevalent in cancer (Aaltomaa et al, 1999;Anttila et al, 1998;Clevers and Nusse, 2012;Gofuku et al, 1999;Lifschitz-Mercer et al, 2001;Matsui et al, 1994;Nakopoulou et al, 2002;Polakis, 2000;Richmond et al, 1997;Rimm et al, 1995;Shiozaki et al, 1994;Silvis et al, 2011;Tanaka et al, 2003;van Oort et al, 2007;Yang et al, 2006). This additional level of regulation by α-catenin may help explain why WNT stimulation has been reported to decrease the sensitivity of cells to DNA damage despite increased nuclear β-catenin levels (Chandra et al, 2015;Chen et al, 2007;Jun et al, 2016;Woodward et al, 2007), and why different experimental systems have had confounding results (Chevillard-Briet et al, 2014;Orford et al, 1999;Tao et al, 2015;Watson et al, 2010). Intriguingly, p53 is able to regulate WNT ligand production in a cell type-dependent manner (Lee et al, 2010) as well as β-catenin levels (Kim et al, 2011; Sadot Our results suggest that the effect of WNT stimulation on the DNA damage response may depend on the levels of nuclear α-catenin, as well as those of β-catenin and other proteins recruited to this complex.…”
Section: Discussionmentioning
confidence: 98%
“…Zhao and colleagues observed that an upregulation of the Wnt/β-catenin pathway accelerates mucosal repair following radiotherapy-induced oral mucositis (33). Very recently, Chandra and colleagues demonstrated that an activated Wnt/β-catenin pathway blocks radiation-induced apoptosis in osteoblasts through enhanced DNA repair, suggesting that Wnt agonists may be clinically used to block radiation-induced osteoporosis (34). In a similar attempt, we stimulated phenotypically “normal” RPE-1 cells, which are highly sensitive to irradiation, with Wnt-3a, a physiological ligand of the Frizzled receptor family.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, an increase was seen in D q in β-catenin overexpressed CNE-2 cells, as revealed by the cell survival curve, indicating the enhanced ability in the repair of sublethal cellular damages, and this may be associated with the overexpression of β-catenin. It was found that activation of the β-catenin pathway effectively promoted the repair of DNA double strand breaks (DSBs) in irradiated osteoblasts [41], and up-regulation of β-catenin expression increased the capacity of DSB repair in cancer cells [42].It is therefore considered that the role of β-catenin in DNA damage repair may be a factor affecting cellular radiation sensitivity.…”
Section: Discussionmentioning
confidence: 99%